Substance-induced mood disorders: a scoping review - Kivlichan, Ashley E.; Praecht, Angela; Wang, Cindy; George, Tony P. (Current addiction reports, 2024)
Substance-induced mood disorders (SIMDs) are an understudied area with a limited published literature. This scoping review evaluated published evidence to determine differences between SIMDs and independent mood disorders with comorbid SUD.
Published online: 2 January 2024
Gesehen am 24.06.2024